Naturally selected CD7-directed CAR-T bridging allo-HSCT in refractory acute myeloid leukemia: a case report and review - Liu, Xuan; Xu, Zheng; Li, Shuhui; Zhang, Xuejun; Li, Jianqiang; Li, Hang; Wang, Fuxu (Frontiers in Immunology, 2024)
Relapsed/refractory acute myeloid leukemia (R/R-AML) have poor prognosis. CD7 is expressed in leukemic cells in 30% of patients with AML and not on normal myeloid cells. Therefore, it can be a potential target for immunotherapy in patients with R/R-AML. Naturally selected CD7 directed chimeric antigen receptor T cell (CAR-T) has promising effects against AML based on xenotransplantation models. We report a R/R-AML case that achieved complete remission with incomplete hematologic recovery with naturally selected CD7 CAR-T therapy. After allogeneic hematopoietic stem cell transplantation (allo-HSCT) as consolidation early after CAR T, the patient acquired 12 months of disease-free survival. Our results confirmed that allogeneic hematopoietic stem cell transplantation after naturally selected CD7 CAR-T therapy can be a potential treatment for patients with CD7 positive R/R-AML.